Almanac for the Anthropocene : A Compendium of Solarpunk Futures - Wieland, Brontë Christopher; Wagner, Phoebe; Project Muse. (Morgantown : West Virginia University Press, 2022)
"Original voices from across the solarpunk movement, which positions ingenuity, generativity, and community as ways to resist hopelessness in response to the climate crisis.Almanac for the Anthropocene collects original voices from across the solarpunk movement, which positions ingenuity, generativity, and community as beacons of resistance to the hopelessness often inspired by the climate crisis. To point toward practical implementation of the movement's ideas, it gathers usable blueprints that bring together theory and practice. The result is a collection of interviews, recipes, exercises, DIY instructions, and more-all of it amounting to a call to create hope through action.Inspired by a commitment to the idea that there can be no environmental justice without decolonial and racial justice, Almanac for the Anthropocene unites in a single volume both academic and practical responses to environmental crisis"--
"Unites both academic and practical responses to environmental crisis from original voices across the solarpunk movement, which positions ingenuity, generativity, and community as ways to resist hopelessness in response to the climate crisis"--
Machine generated contents note: Introduction: The Situation So Far -- Phoebe Wagner and Brontë Christopher WielandPart 1: GenerativityNot Just Solar: Creating Our Own Powers, Stories, and Spaces -- Brontë Christopher Wieland1. Solarpunk Is a Verb for Rising -- The Commando Jugendstil and Tales from the EV Studio2. In Defense of Hope -- Margaret Killjoy3. Feeding Imagination -- Giulia Lepori and Michał Krawczyk4. A Collective Gardening Shed of Concepts for Planting Solarpunk Futures -- Christoph D. D. RupprechtPart 2: IndependenceBuilding toward Autonomy: Ways of Reclaiming the Present and the Future -- Brontë Christopher Wieland5. Your Mineral Footprint -- Gabriel Aliaga6. Solarpunk Design Guidelines -- Navarre Bartz7. How to Build a Solar-Powered Website -- Kris De Decker8. Solarpunks See the World: Traversing the World without Destroying It -- Craig StevensonPart 3: Community"All Organizing Is Science Fiction": On Dreaming a Solarpunk Community -- Phoebe Wagner9. Science Fiction and Disability: Engage! -- Petra Kuppers10. The Urban Reef: Breaking Down Barriers between Green Spaces in Urban Environments -- Octavia Cade11. The Commensal Canine -- Susan Haris12. Solarpunk: The Fruitful Revolution -- Connor D. LouisellePart 4: IngenuitySolarpunk Ingenuity and DIY Projects -- Phoebe Wagner13. Visible Mending: A Recipe for Beautiful and Sustainable Clothing -- Sari Fordham14. Appalachian Solarpunk: Growing Trees from Seed for the Plant Revolution -- Vance Mullis and Joy Lew15. Anthrocene Strategy: Foraging -- Michael J. DeLuca16. Multispecies Community Garden: A More-Than-Human Design Concept Proposal 00 -- for Well-Being in Shrinking Cities -- Christoph D. D. Rupprecht, Aoi Yoshida, and Lihua CuiConclusion: Looking Forward -- Phoebe Wagner and Brontë Christopher WielandContributors.
Description based on print version record.
Includes bibliographical references.
eBooks on EBSCOhost
Keywords: Sustainable living; Ecocriticism; Environmentalism; Style de vie durable; Écocritique.; Environnementalisme; SOCIAL SCIENCE / Future Studies; NATURE / Environmental Conservation & Protection; Sustainable living; Environmentalism; Ecocriticism